2017
DOI: 10.1055/s-0037-1608801
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome in Primary Sclerosing Cholangitis: Current Evidence and Potential Concepts

Abstract: The close relationship between primary sclerosing cholangitis (PSC) and inflammatory bowel disease has inspired hypothetical models in which gut bacteria or bacterial products are key players in PSC pathogenesis. Several studies using high-throughput sequencing technology to characterize the gut microbiota in PSC have been published over the past years. They all report reduced diversity and significant shifts in the overall composition of the gut microbiota. However, it remains unclear as to whether the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 194 publications
(299 reference statements)
1
57
0
5
Order By: Relevance
“…Interestingly, colectomy prior to PSC diagnosis is associated with decreased risk for liver transplantation or death 35. While positive family history and male gender are well-established risk factors for PSC,36 accumulating evidence points to a role of gut microbiota in disease pathogenesis 37. In PSC, several cross-sectional studies demonstrated a reduced gut alpha diversity and significant alterations in the overall microbiota composition compared with healthy controls 17–19.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, colectomy prior to PSC diagnosis is associated with decreased risk for liver transplantation or death 35. While positive family history and male gender are well-established risk factors for PSC,36 accumulating evidence points to a role of gut microbiota in disease pathogenesis 37. In PSC, several cross-sectional studies demonstrated a reduced gut alpha diversity and significant alterations in the overall microbiota composition compared with healthy controls 17–19.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is negatively associated with PSC in patients with concomitant inflammatory bowel disease . Meanwhile, evaluation of the microbiome has generally demonstrated overall inconsistent results except for evidence of reduced alpha diversity in the majority of studies …”
Section: Past Studies On the Environmental Causes Of Liver Diseasementioning
confidence: 99%
“…The close relationship with IBD is the basis of several important hypotheses of PSC pathogenesis. Recent studies have identified an altered gut microbiota in PSC patients, both in stool and the mucosa . It has previously been hypothesized that leakage of bacterial products across an impaired mucosal barrier in the gut could contribute to the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified an altered gut microbiota in PSC patients, both in stool and the mucosa. 4 It has previously been hypothesized that leakage of bacterial products across an impaired mucosal barrier in the gut could contribute to the disease. The liver is continuously exposed to a large variety of substances, including nutrients, gut bacteria and bacterial products originating from the gut via the portal circulation.…”
Section: Introductionmentioning
confidence: 99%